Young Adult Obesity Prevalence and Associated Risk Factors, A Cross-Sectional Anthropometric Study in local Population - Sheeba Faryal, Rizwana Hussain, Iram Fayyaz, Muhammad Saqib Habib, Arjan Kuman, Naveed Shuja, Arslan Shuja (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study was carried out to assess the prevalence of overweight, obesity, and risk factors among young adults in Pakistan. Study Design: A cross-sectional anthropometric study in local population to assess the prevalence of overweight, obesity, and risk factors among young male and female. Place and Duration: Present study was conducted in 25 high schools of Lahore, Islamabad and Karachi from January 2022 to November 2022. Methodology: In this study 1000 young adults (500 girls and 500 boys) of age 15-17 years were selected and used population-based stratified cluster sampling method. To determine the prevalence of overweight and obesity, the participant’s body mass indices (BMI) were compared to the BMI guidelines for Pakistani children and adolescents. In order to gather information about the study group’s sociodemographic traits, Internet use, TV watching, physical activity, and family history of obesity, a standardized questionnaire was administered. Results: According to the findings, there were 8.9% of teenagers who were obese overall (9.6% of females and 7.2% of boys). It was shown that BMI went up when computer use did. Compared to their peers who were of normal weight, a higher percentage of overweight and obese teenagers watched TV and used computers for longer than two hours each day. It was discovered that the patients with normal weight participated more frequently in regular physical activity. 59.6% of the households of overweight adolescents were obese. Practical Implication:It will spread awareness among community about obesity prevalence in young adults and the risk factors associated with them ,controlling methods and things to prevent. Conclusion: Comparatively it was concluded that Pakistan has lower frequency of adolescent obesity than several developed countries. The usage of computer, mobile, television, physical exercise, and family dynamics are all significant risk factors for obesity. Keywords: Adolescent, Obesity, Body mass indices, Risk factors, Anthropometric